Financial statement analysis - Subramanyam, K. R. (Chennai, India Mcgraw Hill education (India) Pvt. Ltd., 2024)
The ability to understand and analyze financial statements is important to effective decision making by investors, creditors, analysts, consultants and managers. Financial Statement Analysis equips students with the necessary skills to succeed in the increasingly competitive business environment.